Kemampuan Menulis Puisi Dengan Menggunakan Media Serbaneka Oleh Siswa Kelas Viii Smp Negeri Oelneke - Yunita Ane; Metropoly M.J. Liubana; Imaniah Kusuma Rahayu (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
This study aims to deretmine the application of multi-media by students of class VIII SMP Negeri Oelneke, and to determine the ability to write poetry using multi-media by students of class VIII SMP Negeri Oelneke this type of research uses quantitative medhods. The research subject is a student of class VIII B SMP Negeri Oelneke with a total of 17 students and the object of research in the form of a test of the ability to write poetry using various media. Data collection techniques in this study use observation, test, questionnaire. Based on the research, the results of the first meeting and the second meeting of the questionnaire were obtained. Observation of the first meeting there are still many problems found in the learning process activities that the learning process activities have not been running in a conducive manner. This causes the student’s work to not meet the minimum completeness criteria (KKM) and learning to write poetry using various media is categorized as not successful. This can be seen from the average score of the first meeting observation results with a value of 68, it can be categorized that the learning process activities are still lacking. Meanwhile, in the second meeting observation, it was runnig conducive, students were actively involved in learning and students listened to the teacher’s explanation well. This couses most of the students’ workto meet the minimum completeness criteria (KKM) and learning to write poetry using various media is categorized as successful. This can be seen from the average score of the results of the second meeting observation with a value of 85, it can be categorized that the learning process activities have increased. Judging from the results of the guestionnaire, it also shows that all students using various media have increased with a value of 89,05. The results of data analysis can be concluded that at the first meeting and the second meeting the abilyti to write poetry using various media has a positive impact in improving the learning process of writing poetry by eighth grade students of SMP Negeri Oelneke. This can be seen in the average value of students in each meeting. At the meeting, the average score was 69,76, students who completed were 8 students with a completeness percentage of 47,05%, while students who did not complete were 9 students with an incomplete percentage of 52,94%. While the average value of students at the second meeting was 80,41, with the number of students who completed as many as 13 students with a percentage of completeness 76% while students who did not complete as many as 4 students with a percentage of incompleteness 24%. Keywords: Multi-Media Writing Puis,